(untitled) (Ustozlar uchun, 2026)
This article analyzes the efficiency of using dictionaries in translation. It examines different types of dictionaries and their role in ensuring accuracy and clarity. The study also highlights key limitations, such as lack of context and incomplete coverage of modern language. Effective strategies for dictionary use are proposed. The results show that dictionaries improve translation quality when used with proper contextual understanding.